Severe symptoms persist for Up to one year after diagnosis of stage I-III lung cancer: An analysis of province-wide patient reported outcomes. (April 2020) - Hirpara, Dhruvin H.; Gupta, Vaibhav; Davis, Laura E.; Zhao, Haoyu; Hallet, Julie; Mahar, Alyson L.; Sutradhar, Rinku; Doherty, Mark; Louie, Alexander V.; Kidane, Biniam; Darling, Gail; Coburn, Natalie G.
Highlights: Longitudinal population-level analysis of patient-reported outcomes in lung cancer. Most common symptoms include tiredness, dyspnea and poor well-being. Symptom trajectories did not improve with time, even among early stage patients. Younger age, female sex, higher stage and comorbidities predicted severe symptoms. Identify at-risk vulnerable patients for symptom management during cancer journey. Abstract: Objectives: Lung cancer is associated with significant disease- and treatment-related morbidity. The Edmonton Symptom Assessment System (ESAS) is a tool developed to elicit patients' own assessment of the severity of common cancer-associated symptoms. The objective of this study was to examine symptom severity in the 12 months following diagnosis of lung cancer, and to identify predictors of high symptom burden. Materials and Methods: : This was a retrospective population-based cohort study, including patients with stage I-III lung cancer diagnosed between 2007–2016, and who had symptom screening in the 12 months following diagnosis. The proportion of patients reporting severe symptoms (ESAS ≥ 7) in the year following diagnosis was plotted over time. Multivariable regression models were constructed to identify factors associated with severe symptoms. Results: 69, 440 unique symptom assessments were reported by 11, 075 lung cancer patients. Tiredness was the most prevalent severe symptom (47.3 %), followed by shortness of breath (39.4 %) and poor wellbeing (36.5 %) among all disease stages. Patients diagnosed with higher stage disease reported more severe symptoms, but symptom trajectories were similar for all stages in the year following diagnosis. Disease stage (RR 1.10–2.01), comorbidity burden (RR 1.17–1.51), degree of socioeconomic marginalization (RR1.15-1.45), and female sex (RR 1.15–1.50) were associated with reporting severe symptoms in the year following diagnosis. Conclusion: Severe physical and psychological symptoms persist throughout the first year following lung cancer diagnosis, regardless of disease stage. Those at risk of experiencing high symptom burden may benefit from targeted supportive care interventions, including psychosocial support aimed at improving health-related quality of life.